Land. 1 - Yamashita, Kazumi, 1959- (The Land, 2025)
"'One shall live and the other shall die.' The younger sister ran through the fields, happy to live with the father who loved and adored her in the peaceful village under the watchful gaze of the four gods. Her elder twin ran through the mountains, swearing vengeance against the man who abandoned her to the very beasts she was hunting--her own father. When their paths finally cross, the terrible truth of their birth is revealed and An is left with a difficult decision: follow her twin to the mountains and beyond as she so desperately desires, or condemn her for trying to take her most precious person away?"--Back cover.